2014
DOI: 10.1371/journal.pone.0100550
|View full text |Cite
|
Sign up to set email alerts
|

Could Local Dynamic Stability Serve as an Early Predictor of Falls in Patients with Moderate Neurological Gait Disorders? A Reliability and Comparison Study in Healthy Individuals and in Patients with Paresis of the Lower Extremities

Abstract: Falls while walking are frequent in patients with muscular dysfunction resulting from neurological disorders. Falls induce injuries that may lead to deconditioning and disabilities, which further increase the risk of falling. Therefore, an early gait stability index would be useful to evaluate patients in order to prevent the occurrence of future falls. Derived from chaos theory, local dynamic stability (LDS), defined by the maximal Lyapunov exponent, assesses the sensitivity of a dynamic system to small pertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 57 publications
4
56
0
1
Order By: Relevance
“…Increased MLEs correspond to a more chaotic and unstable dynamical system (Kantz & Schreiber, 2004;Bradley & Kantz, 2015). In humans, previous studies found an increase in the MLE during walking in patients with focal cerebellar lesion (Hoogkamer et al 2015) and with moderate neurological gait disorders (Reynard et al 2014). We also showed that increased MLE is detectable when inexperienced barefoot runners transition from shod to barefoot running (Ekizos et al 2017) and when healthy adults walk and run over uneven surfaces (Santuz et al 2018a).…”
Section: Muscle Spindle Feedback Is Required For Stable Locomotionsupporting
confidence: 62%
See 1 more Smart Citation
“…Increased MLEs correspond to a more chaotic and unstable dynamical system (Kantz & Schreiber, 2004;Bradley & Kantz, 2015). In humans, previous studies found an increase in the MLE during walking in patients with focal cerebellar lesion (Hoogkamer et al 2015) and with moderate neurological gait disorders (Reynard et al 2014). We also showed that increased MLE is detectable when inexperienced barefoot runners transition from shod to barefoot running (Ekizos et al 2017) and when healthy adults walk and run over uneven surfaces (Santuz et al 2018a).…”
Section: Muscle Spindle Feedback Is Required For Stable Locomotionsupporting
confidence: 62%
“…) and with moderate neurological gait disorders (Reynard et al . ). We also showed that increased MLE is detectable when inexperienced barefoot runners transition from shod to barefoot running (Ekizos et al .…”
Section: Discussionmentioning
confidence: 97%
“…As a result of impaired sensorimotor control, reduced gait stability is associated with aging (Kang and Dingwell, 2008) and neurological disorders (Ijmker and Lamoth, 2012;Reynard et al, 2014). Musculoskeletal pain has been associated with fall risk (Asai et al, 2015;de Zwart et al, 2015;Kitayuguchi et al, 2015) and may also impact stability.…”
Section: Introductionmentioning
confidence: 99%
“…Lyapunov exponent analysis is becoming an increasingly popular measure for examining the response of the neuromuscular system to small perturbations and therefore it could be a reliable tool for injury prevention and for the design of the work/rest ratio. Scientists have used the kinematic trajectory divergence technique as an early identification tool for individuals who are at risk of falling and to study the ability to resist perturbations in passive dynamic walking models [36][37][38][39]. However, the possible relationship between the low back trajectories divergence and muscle fatigue has not been widely investigated during repetitive lightweight lifting tasks.…”
Section: Discussionmentioning
confidence: 99%